2009
DOI: 10.1186/cc7904
|View full text |Cite
|
Sign up to set email alerts
|

Off hour admission to an intensivist-led ICU is not associated with increased mortality

Abstract: Introduction Caring for the critically ill is a 24-hour-a-day responsibility, but not all resources and staff are available during off hours. We evaluated whether intensive care unit (ICU) admission during off hours affects hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 18 publications
6
56
0
Order By: Relevance
“…However, in one recent study, out-of-hours admissions to three intensive care units were found to have higher illness severity, as measured by APACHE II and SAPS II scores, and this was associated with increased mortality. 17 In our cohort, patients admitted at the weekend who survived the first seven days do not have a higher subsequent mortality rate, but those admitted on Monday take days, at night or out of hours do appear to have a worse outcome even if they survive the first seven days. We postulate that these differences in late mortality are more likely to be explained by variation in initial illness severity, since any in-hospital factors around the time of admission would be expected to have less impact after seven days.…”
Section: Patient and Pre-hospital Factorsmentioning
confidence: 61%
“…However, in one recent study, out-of-hours admissions to three intensive care units were found to have higher illness severity, as measured by APACHE II and SAPS II scores, and this was associated with increased mortality. 17 In our cohort, patients admitted at the weekend who survived the first seven days do not have a higher subsequent mortality rate, but those admitted on Monday take days, at night or out of hours do appear to have a worse outcome even if they survive the first seven days. We postulate that these differences in late mortality are more likely to be explained by variation in initial illness severity, since any in-hospital factors around the time of admission would be expected to have less impact after seven days.…”
Section: Patient and Pre-hospital Factorsmentioning
confidence: 61%
“…7 Beyond the impact of discharge day, evidence from a variety of areas of clinical medicine suggests that the day of the week on which medical care is provided may have a significant impact on health outcomes. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] For patients undergoing elective inpatient surgery, there is evidence that the risk of mortality differs between days of the work week. In the United Kingdom, each day following Monday was associated with an independent increase in the odds of 30-day mortality, with a marked relative increase (compared with Monday) of 44% on Friday and 82% on weekend days.…”
Section: Résumémentioning
confidence: 99%
“…These are especially important in the 'off hours' (4:00 PM to 08:00 AM and the weekend) in the ICU [26]. In one study, the authors stated that implementation of the weaning process on weekends shortened sedation usage and IMV duration [27].…”
Section: Discussionmentioning
confidence: 99%